Лінгвістичне підґрунтя юридичної визначеності - Ажнюк, Л.В. (Мовознавство, 2013)
У статті з погляду юридичної лінгвістики обґрунтовано категорію лінгвальної визначеності, яка реалізується на рівні юридичного дискурсу і являє собою лінгвістичний корелят юридичної визначеності. Застосування категорії лінгвальної визначеності проілюстровано на прикладах кількох фрагментів лінгвістичних експертиз юридичних текстів. The article offers a linguistic explanation and theoretical justification of a special category of linguistic certainty which is the reflection of the category of legal certainty in the juridical discourse. The application of this category is instrumental for the development of the methods of the linguistic examination of the disputed textual material in particular and forensic linguistics methodology in general. A starting point of the linguistic expert examination is the presumption of the communicative sufficiency of the juridical text and its linguistic adequacy. A number of lower ranking presumptions derive from this presupposition, namely the presumption of lexical and grammatical unambiguity of the verbal communication means, the presumption of the stylistic homogeneity of the text, the presumption of the relevance of the marked linguistic means etc. The paper argues that the linguistic argumentation of the expert opinion is based on the cognitive models of the reception of the juridical text. The examples of concrete expert examinations are provided as the illustrations of the practical application of the principle of linguistic certainty. The application of the principle of linguistic certainty in forensic linguistics will enable formalization of the analytical methods and its refinement of the acceptable for jurisprudence cognitive models.